Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Wang, Rui (2023)
Quorum quenching (QQ) has been demonstrated to be a novel technique for controlling biofouling in membrane bioreactors (MBRs), as it can significantly inhibit biofilm formation by disrupting quorum sensing (QS). The exploration of new QQ bacterial strains and the evaluation of their performance in mitigating membrane fouling in MBR systems is significant. In this study, an efficient QQ strain, Brucella sp. ZJ1 was encapsulated in alginate beads and evaluated for its ability to mitigate biofouling. The findings revealed that MBR with QQ beads extended the operation time by 2-3 times without affecting pollutant degradation. QQ beads maintained approximately 50% QQ activity after more than 50 days operation, indicating a long-lasting and endurable QQ effect. The QQ effect reduced extracellular polymeric substance (EPS) production especially in terms of polysaccharide and protein by more than 40%. QQ beads in the MBR also reduced the cake resistance and the irreversible resistance of membrane biofouling. Metagenomic sequencing suggests that QQ beads suppressed the QS effect and increased the abundance of QQ enzyme genes, ultimately inducing efficient membrane biofouling control.